Julius Nyerere, Comprehension of Slavery, and Nation Building: Some Notes on Popular Consciousness in Modern Tanzania - BANSHCHIKOVA Anastasia Alekseevna (Ученые записки Института Африки Российской академии наук)
This article examines the image of Julius Nyerere, the first president of independent Tanzania, among present-day citizens. Spotting of both the presence and persistence of his image in popular consciousness became an unexpected result of unrelated field research on the historical memory of 19th century slave trade and its influence on interethnic relations in the country. The study did not include any questions about Julius Nyerere, colonialism, or Tanzania's independence. However, many respondents on their own will start talking about Nyerere's role in connection with the abolition of the slave trade (sic), about his contribution to building a peaceful nation without ethnic tensions, the spread of the Swahili language, and education. The variety of answers shows that almost any positive shift in the development of Tanganyika and Tanzania can be attributed to him in popular consciousness. This demonstrates the continuing importance of Nyerere's image and legacy for ordinary Tanzanians.